Bandung Gardening: Hydroponic Salads - Latue, Theochrasia; Latue, Philia Christi; Rakuasa, Heinrich (Nusantara Journal of Behavioral and Social Science, 2023)
Urban agriculture not only plays an important role in creating sustainable cities but also influences the spatial structure of urban landscapes and communities. One of the small-scale (community) urban agriculture activities is community gardening. In Bandung City, this activity was initiated by the Bandung Gardening community. One of the work programs that can be done for the Bandung gardening community is to make a hydroponic salad. Hydroponics is the cultivation of plants using water without using soil. This research used a descriptive qualitative approach.  The results showed that hydroponics is an efficient and effective method to produce high-quality salads in an urban environment like Bandung. Hydroponic plants tend to grow faster than those in soil, with higher yields and better nutritional quality. The success of this hydroponic technique is supported by the reduced use of water and less land compared to traditional farming. Hydroponic systems work by allowing control over environmental conditions, such as temperature, pH balance, and maximizing exposure to nutrients and water. Despite being grown in a water medium, hydroponic farming can actually save water. This is because the water used is not absorbed by the soil. The water is absorbed by the plants better. Hydroponic farming is also more energy-efficient because it is done without non-renewable energy such as electricity. Abstrak: Pertanian perkotaan tidak hanya memainkan peran penting dalam menciptakan kota yang berkelanjutan tetapi juga mempengaruhi struktur spasial lanskap perkotaan dan masyarakat. Salah satu kegiatan pertanian perkotaan skala kecil (masyarakat) berupa kebun masyarakat. Di Kota Bandung kegiatan ini digagas oleh komunitas Bandung Gardening. Salah satu program kerja yang dapat dilakukan untuk komunitas berkebun Bandung adalah membuat salad hidroponik. Hidroponik adalah budidaya tanaman dengan menggunakan air tanpa menggunakan tanah. Penelitian ini menggunakan pendekatan kualitatif deskriptif.  Hasil penelitian menunjukkan bahwa hidroponik merupakan metode yang efisien dan efektif untuk menghasilkan salad berkualitas tinggi di lingkungan perkotaan seperti Bandung. Pertumbuhan tanaman hidroponik cenderung lebih cepat daripada yang dalam tanah, dengan hasil panen yang lebih tinggi dan kualitas nutrisi yang lebih baik. Keberhasilan teknik hidroponik ini didukung oleh pengurangan penggunaan air dan lahan yang lebih sedikit dibandingkan dengan pertanian tradisional. Sistem hidroponik bekerja dengan memungkinkan kontrol atas kondisi lingkungan, seperti suhu, keseimbangan pH, dan memaksimalkan paparan nutrisi dan air. Meski ditanam di media air, bercocok tanam hidroponik sebenarnya bisa menghemat air. Hal ini dikarenakan air yang digunakan tidak terserap oleh tanah. Air diserap oleh tanaman lebih baik. Pertanian hidroponik juga lebih hemat energi karena dilakukan tanpa energi tak terbarukan seperti listrik.